Zizania latifolia Cell Wall Polysaccharide Metabolism and Changes of Related Enzyme Activities during Postharvest Storage - Jing Huang; Weijie Wu; Xiangjun Fang; Hangjun Chen; Yanchao Han; Ben Niu; Haiyan Gao (Foods, 2022)
The metabolism of polysaccharides in the Zizania latifolia cell wall helps maintain the postharvest quality during storage. Fresh Z. latifolia was stored at 4 °C and 25 °C to evaluate the hardness, cell wall polysaccharide composition, cell wall structure, active ingredients, and cell wall metabolism-related enzyme activities. The results showed that hardness declined concomitantly with an increase in water-soluble pectin content during storage, as well as with a decrease in propectin and cellulose contents. Correlation analysis showed that lower activities of cell wall-degrading enzymes, such as polygalacturonase, cellulase, and β-galactosidase in Z. latifolia stored at 4 °C, were associated with lighter fiberization and greater hardness, compared with those stored at 25 °C. Additionally, the results of infrared spectroscopy showed that texture softening may be attributed to a decrease in the degree of esterification of water-soluble polysaccharides at 25 °C compared to that at 4 °C.